Governance and institutional autonomy: governing and governance in portuguese higher education - António M. Magalhães (2013)
This paper aims at looking at governance instruments beyond managerial technicality. It intends to do so by analysing the impact of governance reforms on the universities autonomy assumed as a regulation instrument to politically steer systems and institutions. The regulation efforts undertaken at the European and national levels reflect a trend towards coordination of devolved governance processes (meta-governance). Although there is a wide consensus about awarding autonomy to universities and increasing self-governance, governments need to ensure that their goals are actually pursued, enhancing their regulation frames and meta-governance efforts. This paper focuses on how the governance reform interacts with institutional contexts. The changes promoted by the governance reform are an opportunity to understand how far these apparently contradictory forces operate in three selected Portuguese universities with regard to institutional autonomy.